A decaying neutralino as dark matter and its gamma ray spectrum - Amin Aboubrahim; Tarek Ibrahim; Michael Klasen; Pran Nath (European Physical Journal C: Particles and Fields, 2021)
Abstract It is shown that a decaying neutralino in a supergravity unified framework is a viable candidate for dark matter. Such a situation arises in the presence of a hidden sector with ultraweak couplings to the visible sector where the neutralino can decay into the hidden sector’s lightest supersymmetric particle (LSP) with a lifetime larger than the lifetime of the universe. We present a concrete model where the MSSM/SUGRA is extended to include a hidden sector comprised of $$U(1)_{X_1} × U(1)_{X_2}$$ U ( 1 ) X 1 × U ( 1 ) X 2 gauge sector and the LSP of the hidden sector is a neutralino which is lighter than the LSP neutralino of the visible sector. We compute the loop suppressed radiative decay of the visible sector neutralino into the neutralino of the hidden sector and show that the decay can occur with a lifetime larger than the age of the universe. The decaying neutralino can be probed by indirect detection experiments, specifically by its signature decay into the hidden sector neutralino and an energetic gamma ray photon. Such a gamma ray can be searched for with improved sensitivity at Fermi-LAT and by future experiments such as the Square Kilometer Array (SKA) and the Cherenkov Telescope Array (CTA). We present several benchmarks which have a natural suppression of the hadronic channels from dark matter annihilation and decays and consistent with measurements of the antiproton background.